PENINGKATAN KETERAMPILAN BERBICARA DALAM BAHASA INGGRIS BERBASIS PARIWISATA BAGI SISWA SD DI DESA HUTARAJA - putri sari silaban (Jurnal Mitra Prima, 2020)
Abstract English language speaking mastery is a basic need for people who rely on the tourism sector. Just like people who live in Hutaraja, this need is crucial to them in selling their creation to the tourists moreover to the foreign tourist who often visit Hutaraja. Sadly, this chance must be faced by the people of Hutaraja who do not master any English language speaking mastery. This problem encouraged to the implementation of this training. This training had given positive result to Hutaraja’s people English language speaking mastery. However, further training is needed in order to enhance English language speaking mastery of people in Hutaraja so that they can have better insight and better English language speaking mastery in communicating with foreign tourists who visit Hutaraja. Keywords: Training; Basic Skills; Speaking; English